Cr3C2-Co composite powder and preparation method thereof

By using Cr3C2-Co composite powder in cemented carbide, the problems of uneven dispersion of existing inhibitors and poor inhibition effects are solved through carbon-heat reduction and wet grinding technology, and better WC grain control and improved performance of cemented carbides are achieved.

CN119549700APending Publication Date: 2025-03-04WUHAN XINRUI ALLOY TOOLS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411662598.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing Cr3C2 grain growth inhibitors have uneven dispersion and poor inhibition effect, making it difficult to prepare nano/ultrafine carbides with high hardness and good toughness.

Method used

By simultaneously reducing the oxide of Cr and the oxide of Co or their oxides precursors of Cr, Cr3C2-Co composite powder is prepared, and wet grinding and high-temperature reaction technology can achieve uniform dispersion and pre-dissolving of Cr3C2 in Co, optimizing its inhibitory effect.

Benefits of technology

The uniform dispersion of Cr3C2 is achieved, which enhances its effect of inhibiting WC grain growth and improves the coercive force, hardness and density of cemented carbide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549700A_ABST
    Figure CN119549700A_ABST
Patent Text Reader

Abstract

The invention discloses Cr3C2-Co composite powder and a preparation method of the Cr3C2-Co composite powder, the Cr3C2-Co composite powder is composed of two substances of Cr3C2 and Co, and the weight percentage of the Cr3C2 is 5-95%. The preparation method of the Cr3C2-Co composite powder is characterized in that a carbon thermal reduction oxide or an oxide precursor is adopted, and the preparation method comprises the following steps that S1, the oxide or the oxide precursor and carbon black or a precursor capable of being decomposed into the carbon black are subjected to ball milling and mixing under the protective atmosphere or in a wet milling medium, and mixed powder with refined particle size and uniform mixing is obtained; s2, drying in vacuum or N2; s3, carrying out high-temperature reaction in Ar and H2 or in vacuum; and S4, carrying out ball-milling crushing or jet milling, and carrying out size grading on the powder. Compared with traditional Cr3C2 powder, the preparation temperature of the Cr3C2-Co composite powder with the same granularity is 150-200 DEG C lower than that of traditional Cr3C2 powder, non-uniform growth of WC grains in WC-Co-based hard alloy can be more effectively inhibited, and the hardness, strength and toughness of the superfine / nanocrystalline hard alloy material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of powder metallurgy, relates to hard alloy raw materials, and specifically relates to a Cr3C2-Co composite powder and a preparation method thereof. Background Art

[0002] Carbide cutting tools have high hardness, high wear resistance and good toughness, and are known as the "teeth of industry". As an important component, WC, when its grain size is less than 0.5μm, the hardness and toughness of the alloy will be greatly improved, and as the grain size further decreases, the improvement will be more obvious. However, in order to prepare "double high" cemented carbide with both high hardness and good toughness, the structure of the cemented carbide must meet the requirements of uniform composition and uniform grain size. Since the WC powder raw material used to prepare nano / ultrafine cemented carbide has a large specific surface area and active properties, the WC grains grow rapidly during the sintering process, which becomes the biggest obstacle in the preparation of nano / ultrafine cemented carbide.

[0003] In order to prepare WC-Co cemented carbide with excellent comprehensive performance, the control of WC grain size and distribution, WC grain morphology and sintering technology are crucial. Grain growth inhibitors are usually added to prevent abnormal grain growth. Among the many types of inhibitors, Cr3C2 is a relatively effective WC grain growth inhibitor, which is due to its high solubility and fluidity in the cobalt binder phase. Adding Cr3C2 can improve the transverse fracture strength of cemented carbide.

[0004] However, the existing Cr3C2 grain growth inhibitors still have the problems of uneven dispersion and poor inhibitory effect. The research content of the present invention is how to provide an inhibitor with more uniform dispersion and better inhibitory effect. Summary of the invention

[0005] The invention provides a Cr3C2-Co composite powder and a preparation method thereof, in order to solve the problems of uneven dispersion and poor inhibition effect of existing inhibitors.

[0006] To achieve the above-mentioned object, the present invention provides a Cr3C2-Co composite powder: composed of Cr3C2 and Co, the Cr3C2-Co composite powder is prepared by simultaneous carbon thermal reduction of a Cr source and a Co source, the Cr source is Cr oxide and / or a Cr oxide precursor, and the Co source is Co oxide and / or a Co oxide precursor.

[0007] The present invention also provides a method for preparing Cr3C2-Co composite powder, comprising the following steps:

[0008] S1: ball-milling the Cr source, the Co source and the C source under a protective atmosphere or in a wet grinding medium to obtain a mixed powder with refined particle size and uniform mixing, wherein the degree of particle size refinement is 0.1-0.9 of the original particle size;

[0009] S2: Dry the mixed powder in vacuum or N2;

[0010] S3: subjecting the dried powder to a high temperature reaction under Ar, H2 or vacuum, the reaction temperature being 750-1100°C;

[0011] S4: Ball milling or jet milling to classify the powder.

[0012] The relevant contents in the above technical solution are explained as follows:

[0013] 1. In the above scheme, in the Cr3C2-Co composite powder, the mass percentage of Cr3C2 is 5-95%.

[0014] 2. In the above scheme, the Cr oxide is one or a mixture of CrO, Cr2O3, CrO2, CrO3.

[0015] 3. In the above scheme, the Co oxide is one or a mixture of CoO (cobalt oxide), Co2O3 (cobalt-rich oxide), Co3O4 (cobalt trioxide).

[0016] 4. In the above scheme, the Cr oxide precursor is decomposed at high temperature to obtain gas and Cr oxide, and the Cr oxide precursor is one or a mixture of Cr hydroxide, oxalate, acetate.

[0017] 5. In the above scheme, the Co oxide precursor is decomposed at high temperature to obtain gas and Co oxide, and the Co oxide precursor is one or a mixture of Co hydroxide, oxalate, acetate.

[0018] 6. In the above scheme, the Cr source is Cr oxide and / or Cr oxide precursor, and the Co source is Co oxide and / or Co oxide precursor.

[0019] 7. In the above scheme, the C source is a precursor that decomposes into carbon black after high-temperature reaction, and can be decomposed into solid carbon and gas, including glucose, sucrose, coconut shell, starch, bamboo, straw, and wood.

[0020] 8. In the above scheme, in S1, the protective atmosphere refers to an inert gas atmosphere or a nitrogen atmosphere, and the inert gas is Ar and / or He.

[0021] 9. In the above scheme, the wet grinding media refers to the three types of pure water, industrial alcohol and n-hexane used in the industry, among which the ethanol concentration in industrial alcohol is 90-99.5%.

[0022] 10. In the above scheme, there is no specific degree or standard for particle size refinement. For the same raw material, the degree of refinement is different when ball milled for different mixing time (generally 10h-70h). The mixing time can be adjusted according to the needs of the product particle size.

[0023] 11. In the above scheme, there is no fixed standard for particle size classification. Classification can be carried out according to demand, such as below 0.5μm, 0.5-1μm, 1-3μm, 3-45μm, 45-75μm, 75-150μm, and above 150μm.

[0024] 12. In the above scheme, the carbon thermal reduction is carried out under protective atmosphere or in a wet grinding medium at 750-1100°C.

[0025] Working principle of the present invention:

[0026] At present, there are no papers or patents reporting on Cr3C2-Co composite powder. It is only found that Chinese Patent Publication No. CN116043088A (application date 2023.01.17) provides a carbide composite powder precursor and its preparation method. This method uses an iron group metal organic alkoxide solution to mix, dry and calcine with carbide to prepare a carbide composite powder precursor. If Cr3C2-Co composite powder is prepared, the method will use Cr3C2 and Co organic alkoxide solution to mix and then dry and calcine to prepare a Cr3C2-Co composite powder precursor. Although this method has similarities with the patent in terms of steps, the types of raw materials are completely different.

[0027] Studies have shown that the formation energy of (W,Cr)Cx is higher than that of WCx, so Cr3C2 exists in the bonding phase but not at the WC / Co interface. Cr3C2 preferentially dissolves in the Co phase, greatly reducing the solubility of WC in the Co phase, thereby slowing down the growth of WC grains through liquid phase recrystallization. When Cr3C2-Co composite powder is prepared at high temperature, Cr3C2 is pre-dissolved in Co, which optimizes the dispersion of Cr3C2 and strengthens its inhibitory effect. In addition, the low eutectic point of Cr3C2-Co also makes the liquid phase appear earlier in the cemented carbide during the sintering process, accelerating the densification of the alloy.

[0028] In the present invention, the process of preparing Cr3C2-Co composite powder by high temperature reaction is divided into several stages: first, the oxide precursor and the carbon black precursor decompose to generate gas, carbon black, and oxide. Under the action of flowing gas or vacuum, the gas is discharged, leaving solid carbon black and oxide. This process occurs below 300°C; secondly, the cobalt oxide is reduced, the gas product is discharged, leaving solid cobalt and chromium oxide. This process occurs at 350°C-500°C; then, as the temperature rises, cobalt diffuses into carbon black and chromium oxide, promoting the contact between carbon black and chromium oxide. Oxygen atoms diffuse into cobalt and react with carbon black, thereby promoting the removal of oxygen from chromium oxide. This process occurs at 550°C-1000°C; finally, the reduced product chromium reacts with carbon black to generate Cr3C2. This process occurs at 750°C-1100°C; in addition, under the action of high temperature, the product Cr3C2 will diffuse into cobalt, forming a sintering neck on the contact surface, increasing the contact area.

[0029] In summary, by simultaneously carbon thermally reducing Cr oxide and Co oxide or their oxide precursors, the reduction temperature of Cr oxide can be lowered, the diffusion of Cr3C2 into cobalt can be promoted, and Cr3C2 and cobalt form a sintering neck at the contact surface, which is conducive to the uniform dispersion of Cr3C2 during wet grinding. By adjusting the ratio of Cr oxide and Co oxide or the ratio of their oxide precursors in the raw material, and adjusting the content of carbon black or a precursor that can be decomposed into carbon black, Cr3C2-Co composite powders with different Cr3C2 contents can be obtained.

[0030] Compared with the prior art, the above solution of the present invention has the following advantages:

[0031] 1. Pre-mixed Cr3C2 and Co powders were prepared, which was beneficial to the uniform dispersion of Cr3C2.

[0032] 2. Lowering the reduction temperature of Cr oxide is more conducive to the preparation of Cr3C2 with finer particle size.

[0033] 3. Under the same particle size conditions, after the same preparation process of the present technical solution (Cr3C2-Co composite powder) and the prior art (Cr3C2 powder), the alloy obtained by the present technical solution has higher coercive force, hardness and density. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is the electron microscope morphology of the powder mixture before high temperature reaction and the electron microscope morphology of the Cr3C2-Co composite powder after high temperature reaction in Example 1 of the present invention (10000 times).

[0035] Figure 2 It is the electron microscope morphology picture (10000 times and 20000 times) of the Cr3C2-Co composite powder in Example 2 of the present invention. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0037] The attached figures mainly involve products in the range of 1-3μm.

[0038] Embodiment 1:

[0039] Cr2O3, Co3O4 and micron-sized carbon black were used as raw materials, and mixed in a ball mill under Ar atmosphere for 20 hours according to the stoichiometric ratio that the Co content in the product after carbon thermal reduction was 20wt.%. The mixed powder was placed in a boat, reacted at 1000℃ under vacuum for 4 hours, and then cooled naturally. The reaction product cooled to below 50℃ was ball milled in a horizontal ball mill for 5 hours and sieved with a 200 mesh.

[0040] Embodiment 2:

[0041] Cr2O3, Co3O4, CoO and sucrose are used as raw materials, and the Co content in the product after decomposition into carbon accounts for 25wt.% in the stoichiometric ratio. Anhydrous alcohol is used as the wet grinding medium and the mixture is ball-milled in a horizontal ball mill under Ar atmosphere for 30 hours. The alcohol addition amount is 1000ml / kg, and the ball milling balls are WC-6wt.%Co cemented carbide with a diameter of 8mm. After the mixed slurry is passed through 325 mesh, it is dried and stirred in a vacuum drying equipment until it is completely dry, and then filled with Ar to atmospheric pressure and cooled to below 50°C. The cooled powder is placed in a boat, reacted at 1100°C in a H2 atmosphere for 4 hours, and then cooled naturally. After the reaction product is cooled to below 50°C, it is ball-milled in a horizontal ball mill for 5 hours, sieved with a 200 mesh, and then crushed for the second time with a jet mill. The microscopic morphology of the prepared powder can be seen. Figure 2 The average particle size is 1.0 μm. The WC-10Co-0.5Cr3C2 alloy is prepared by the same process as the Cr3C2 (particle size 0.8 μm) on the market, wherein the particle size of WC and Co powder is 0.8 μm, and the properties of the alloy are shown in the following table. The alloy prepared by the present invention has higher coercive force and hardness than the alloy prepared by the commercial Cr3C2 under the condition of basically the same magnetic saturation, indicating that the inhibitor of the present invention is better in terms of inhibitory effect.

[0042]

[0043]

[0044] Embodiment 3:

[0045] Cr2O3 (average particle size 2μm), Co3O4 (average particle size 10μm), and carbon black (average particle size 0.5μm) are used as raw materials. According to the stoichiometric ratio that the Co content in the product after complete reaction accounts for 20wt.%, anhydrous alcohol is used as the wet grinding medium in a horizontal ball mill under Ar atmosphere for 50h, wherein the alcohol addition amount is 1000ml / kg, and the ball milling ball is WC-6wt.%Co cemented carbide with a diameter of 8mm. After the mixed slurry is passed through 325 mesh, it is dried and stirred in a vacuum drying equipment until it is completely dry, and then filled with Ar to atmospheric pressure and cooled to below 50℃. The cooled powder is placed in a boat, reacted at 1000℃ in a vacuum atmosphere for 2 hours, and then cooled naturally. After the reaction product cooled to below 50℃ is ball-milled in a horizontal ball mill for 2h, it is sieved with a 200 mesh, and then the powder is crushed for the second time using a jet mill. The results of energy spectrum analysis show that the Co content in the powder is 20.12%, which is consistent with the designed content.

[0046] Embodiment 4:

[0047] Cr2O3 (average particle size 5μm), Co3O4 (average particle size 20μm), and carbon black (average particle size 1.0μm) were used as raw materials. According to the stoichiometric ratio that the Co content in the product after complete reaction accounts for 15wt.%, anhydrous alcohol was used as the wet grinding medium in a horizontal ball mill under Ar atmosphere for 12h, wherein the alcohol addition amount was 800ml / kg, and the ball milling ball used was WC-6wt.%Co cemented carbide with a diameter of 8mm. After the mixed slurry was passed through 325 mesh, it was dried and stirred in a vacuum drying equipment until it was completely dry, and then filled with Ar to atmospheric pressure and cooled to below 50℃. The cooled powder was placed in a boat, reacted at 1100℃ in a vacuum atmosphere for 1 hour, and then cooled naturally. After the reaction product cooled to below 50℃ was ball-milled in a horizontal ball mill for 2h, it was sieved with a 200 mesh. The powder was dendritic and had a size of 3 to 5μm. The results of energy spectrum analysis show that the Co content in the powder is 14.67%, which is consistent with the designed content.

[0048] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A Cr3C2-Co composite powder, characterized in that: The Cr3C2-Co composite powder is composed of Cr3C2 and Co. The Cr3C2-Co composite powder is prepared by simultaneously carbon thermal reduction of a Cr source and a Co source. The Cr source is Cr oxide and / or a Cr oxide precursor, and the Co source is Co oxide and / or a Co oxide precursor.

2. The Cr3C2-Co composite powder according to claim 1, characterized in that: In the Cr3C2-Co composite powder, the mass percentage of Cr3C2 is 5-95%.

3. The Cr3C2-Co composite powder according to claim 1, characterized in that: The Cr oxide is one of CrO, Cr2O3, CrO2, CrO3 or a mixture of several thereof.

4. The Cr3C2-Co composite powder according to claim 1, characterized in that: The Co oxide is one of CoO, Co2O3, Co3O4 or a mixture of several thereof.

5. The Cr3C2-Co composite powder according to claim 1, characterized in that: The Cr oxide precursor is one of Cr hydroxide, oxalate and acetate or a mixture of several of them.

6. The Cr3C2-Co composite powder according to claim 1, characterized in that: The Co oxide precursor is one or a mixture of Co hydroxide, oxalate and acetate.

7. A method for preparing the Cr3C2-Co composite powder according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: ball-milling the Cr source, the Co source and the C source under a protective atmosphere or in a wet grinding medium to obtain a mixed powder with refined particle size and uniform mixing, wherein the degree of particle size refinement is 0.1-0.9 of the original particle size; S2: Dry the mixed powder in vacuum or N2; S3: subjecting the dried powder to a high temperature reaction under Ar, H2 or vacuum, the reaction temperature being 750~1100℃; S4: Ball milling or jet milling to classify the powder.

8. The method for preparing Cr3C2-Co composite powder according to claim 7, characterized in that: The Cr source is Cr oxide and / or a Cr oxide precursor, and the Co source is Co oxide and / or a Co oxide precursor.

9. The method for preparing Cr3C2-Co composite powder according to claim 7, characterized in that: The C source is a precursor that decomposes into carbon black after high-temperature reaction, and the C source includes glucose, sucrose, coconut shell, starch, bamboo, straw, and wood.

10. The method for preparing Cr3C2-Co composite powder according to claim 7, characterized in that: In S1, the protective atmosphere refers to an inert gas atmosphere or a nitrogen atmosphere, and the inert gas is Ar and / or He.

Citation Information

Patent Citations

  • Carbide composite powder precursor and preparation method and application thereof

    CN116043088A